Functionalization of the Octahydro-Binaphthol Skeleton: A Universal Strategy for Directly Constructing D–A Type Axially Chiral Biphenyl Luminescent Molecules - Jiang, Aiwei; Cui, Huihui; Zhang, Li; Cao, Chenhui; Dai, Hong; Lu, Chaowu; Ge, Cunwang; Lu, Hongbin; Wu, Zheng-Guang (Journal of organic chemistry, 2024)
D–A type axially chiral biphenyl luminescent molecules are directly constructed through ingenious functionalization of the octahydro-binaphthol skeleton without optical resolution. The circularly polarized organic light-emitting diodes based on them display remarkable circularly polarized electroluminescence emission, a high luminance of >10 000 cd m–2, a maximum external quantum efficiency of 6.6%, and an extremely low-efficiency roll-off. This work provides a universal strategy for developing efficient and diverse axially chiral biphenyl emitters.